2021
DOI: 10.1021/acs.jpcc.1c02387
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Active Metal Carbide and Nitride Catalytic Facets for Hydrodeoxygenation Reactions

Abstract: The catalytic hydrodeoxygenation (HDO) reaction is of considerable interest for biomass conversion to valuable chemicals and fuels, where one of the critical bottlenecks is the lack of cost-effective and efficient catalysts. To discover cost-efficient catalysts for the HDO reaction, we employed a density functional theory-based hierarchical catalyst design strategy based on catalytic descriptors, reaction energy profiles, and microkinetic modeling (MKM). We focused on the carbide and nitride catalyst space, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…8,9 The development of highly active catalysts for HDO technology is an important factor but still remains a great challenge. Many kinds of catalysts, such as noble metal catalysts, [10][11][12] metal sulde catalysts, 13,14 metal carbide catalysts 15,16 and transition metal catalysts [17][18][19] are widely used. However, noble metal catalysts are not appropriate for industrial utilization because of their high price, difficult availability, poor reusability and easy deactivation caused by carbon deposition.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The development of highly active catalysts for HDO technology is an important factor but still remains a great challenge. Many kinds of catalysts, such as noble metal catalysts, [10][11][12] metal sulde catalysts, 13,14 metal carbide catalysts 15,16 and transition metal catalysts [17][18][19] are widely used. However, noble metal catalysts are not appropriate for industrial utilization because of their high price, difficult availability, poor reusability and easy deactivation caused by carbon deposition.…”
Section: Introductionmentioning
confidence: 99%
“…For the reverse reaction, Haider et al investigated the hydrodeoxygenation of ethanol on metal and bimetallic alloy catalysts using C* and O* as descriptors, where Ir, Ru, Rh, and Ni were found to produce mainly methane, while bimetallic catalysts Co 3 Ni and Ni 3 Fe produced more ethane 80 . Moreover, Assary et al predicted Mo 2 C(111) as a good candidate catalyst for ethylene production from glycolaldehyde hydrodeoxygenation, where the intermediates HOCH 2 CHO* and O* were used as the descriptors 81 . For the n‐butane oxidation reaction, Schweitzer et al identified Ag 3 Pd as a promising nanoparticle composition for selective 1‐butanol production using OH* and C* as descriptors 82 .…”
Section: Applications Of Computational Framework For Catalyst Designmentioning
confidence: 99%
“…The high oxygen content in bio-oils is undesirable and oen removed using hydrodeoxygenation (HDO), a catalytic process in which C-O bond cleavage is carried out in the presence of H 2 gas as the reductant. 2 Transition metal carbides have been considered the promising catalyst candidates for HDO reactions [3][4][5][6][7][8][9] as they are of low cost and, in the case of Mo 2 C, can achieve Pt-like catalytic activity. 7 Furthermore, strategies to modify Mo 2 C catalysts with transition metals to enhance HDO activity has been employed in both experimental and computational studies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, computational screenings of descriptors have been carried out for various catalytic systems including bimetallic alloys, [17][18][19] single-atom catalysts, 20 and transition metal carbides and nitrides 6 via density functional theory (DFT) simulations. Nevertheless, the high cost of DFT calculations remains the bottleneck of high-throughput descriptor generation.…”
Section: Introductionmentioning
confidence: 99%